The effect of herbal medicine in innate immunity to Candida albicans - Bao, Meng-Yuan; Li, Ming; Bu, Qing-Ru; Yang, Yue; Song, Hang; Wang, Chang-Zhong; Wang, Tian-Ming; Li, Ning (Frontiers in Immunology, 2023)
Candida albicans (C. albicans) is an opportunistic pathogenic fungus that often causes mucosal and systemic infections. Several pattern recognition receptors (PRRs), such as Toll-like receptors (TLRs) and C-type lectin receptors (CLRs), have been implicated in the host recognition of C. albicans. These PRRs recognize the pathogen-associated molecular patterns (PAMPs) of C. albicans to activate innate immune cells, thereby rapidly inducing various inflammatory responses by activating intracellular signaling cascades. Herbal medicine and its active components deserve priority development due to their low toxicity and high antibacterial, antiviral and antifungal activities. This review discussed the activities of herbal compounds against C. albicans and their related mechanisms, especially their regulatory role on innate immune cells such as neutrophils, macrophages, and dendritic cells (DCs) implicated in C. albicans infections. Our work aims to find new therapeutic drugs and targets to prevent and treat diseases caused by C. albicans infection with the mechanisms by which this fungus interacts with the innate immune response.